A pilot study investigating changes in neural processing after mindfulness training in elite athletes - Haase, Lori; May, April C.; Falahpour, Maryam; Isakovic, Sara; Simmons, Alan N.; Hickman, Steven D.; Liu, Thomas T.; Paulus, Martin P. (Frontiers in Behavioral Neuroscience, 2015)
The ability to pay close attention to the present moment can be a crucial factor for performing well in a competitive situation. Training mindfulness is one approach to potentially improve elite athletes’ ability to focus their attention on the present moment. However, virtually nothing is known about whether these types of interventions alter neural systems that are important for optimal performance. This pilot study examined whether an intervention aimed at improving mindfulness [Mindful Performance Enhancement, Awareness and Knowledge (mPEAK)] changes neural activation patterns during an interoceptive challenge. Participants completed a task involving anticipation and experience of loaded breathing during functional magnetic resonance imaging (fMRI) recording. There were five main results following mPEAK training: (1) elite athletes self-reported higher levels of interoceptive awareness and mindfulness and lower levels of alexithymia; (2) greater insula and anterior cingulate cortex (ACC) activation during anticipation and post-breathing load conditions; (3) increased ACC activation during the anticipation condition was associated with increased scores on the describing subscale of the Five Facet Mindfulness Questionnaire (FFMQ); (4) increased insula activation during the post-load condition was associated with decreases in the Toronto Alexithymia Scale (TAS) identifying feelings subscale; (5) decreased resting state functional connectivity between the PCC and the